Head Circumference at Birth as a Surrogate Measurement for Identifying Low Birth Weight Newborns - Kusharisupeni; Putra, Wahyu K.Y.; Utari, Diah M.; Fajarini, Isna A. (Pakistan Journal of Nutrition, 2019)
Background and Objective: The number of neonatal morbidity and mortality cases caused by low birth weight (LBW) can be reduced by providing appropriate care immediately after birth. However, in some rural areas, it is hard to detect LBW without the proper tools or equipment. The aim of this study was to find a simple, reliable and suitable surrogate measurement to detect LBW. Materials and Methods: This study was conducted at a maternal clinic in East Jakarta in 2014. All newborns, born during the study period, were included in the study. Birth weight, head circumference (HC) and chest circumference (CC) were measured according to standardized techniques by trained midwives. Receiver Operating Characteristic (ROC) curve analyses were carried out to calculate Area Under Curve (AUC). Results: Out of 100 newborns, 57% were male and 43% were female. The average birth weight was 3223±412.21 g, the average HC was 32.69±1.24 cm and average CC was 32.36±145. HC was identified as the optimal surrogate measurement to identify LBW (AUC: 0.74, 95% CI 0.55-0.92), with a cut-off value of 32.12 cm. Conclusion: We found that HC is a better surrogate measurement to detect LBW than CC. Further studies are required to validate the results in rural community settings.